Introduction to MYOB Accounting Basics in Accounting Data Processing at SMK 2 BM Swasta Medan Putri - Mikha Dayan Sinaga; Nita Sari Br Sembiring; Charles Jhony Mantho Sianturi; Erwin Ginting (JUDIMAS, 2021)
To improve the learning quality of SMK students in the accounting field, various breakthroughs are needed, both in curriculum development, learning innovation, learning media and fulfillment of educational facilities and infrastructure. The use of computers in the learning process is inevitable in today's digital era. The need for computers is increasing rapidly in any field of science, including the field of accounting. Computers can be very helpful in all accounting work which is usually done manually. This can be realized with the help of accounting software, one of which is MYOB Accounting. Today, many students are not very familiar with MYOB as a software that is able to complete work in the accounting field. Students also do not know exactly how to use it. Accounting always contains a count of numbers that are often very large, so they can provide a high error rate when done manually. To find alternative solutions to the problems above, a training on the introduction of MYOB and its benefits in accounting was held. With the aim of training students of SMK 2 BM Swasta Medan Putri to be able to use MYOB and apply it in the accounting field.